INTEGRATION OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PRINCIPLES IN ISLAMIC FINANCE - Ajeng Qurrota A’yun; Lis Yulitasari (CV. Visionary Raya Sakti, 2026)
This study examines the integration of Environmental, Social, and Governance (ESG) principles within Islamic finance through a systematic literature review of research published between 2019 and 2024. Findings indicate a strong conceptual alignment between ESG and maqāṣid al-sharī‘ah, particularly in environmental stewardship, social justice, and ethical governance. Empirical studies show that ESG implementation enhances the sustainability reporting, reputation, and financial stability of Islamic financial institutions, although challenges remain in standardization, human resource capacity, and verification. Green sukuk emerges as the most significant ESG-aligned Islamic financial instrument, contributing to sustainable development and renewable energy financing. Nevertheless, regulatory gaps between global ESG frameworks and Shariah-specific standards hinder optimal adoption. This study concludes that strengthening regulatory harmonization, improving ESG literacy, and enhancing Shariah governance capacities are essential for advancing ESG integration in Islamic finance